Kajian Literatur: Granul Instan dari Bahan Alam Sebagai Antioksidan - Rahadatul Aisy Chaniago (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Instant granules are preparations in the form of granules that are served by brewing and are widely chosen because of their practicality. Natural materials are widely used as antioxidants, but they still need to be made practical for their use. Therefore, this literature review was conducted to provide information regarding the formulation, evaluation of instant granules, and natural ingredients used in instant granules. This research method was carried out by studying literature from various data sources, namely the Directory of Open Access Journals, Science Direct (DOAJ), Garuda, and Google Scholar. A literature search was carried out using several keywords such as "formulation", "instant granules", "natural compounds", "herbs", and "antioxidants". The search results for various natural ingredients with antioxidant effects have been formulated into instant granule dosage forms. The formulation of instant granules is generally carried out using the wet granulation method. Evaluation of preparations carried out were physical evaluation of preparations, hedonic tests, and antioxidant activity tests. The content of phenol group compounds and vitamin C is found in many natural ingredients used in the manufacture of instant granules. The antioxidant activity of combined natural ingredients can provide stronger activity than a single active ingredient. Therefore, the utilization of phenol group compounds from various herbs as antioxidants are expected to continue to be developed.